Role of Government Authorities in The Supervision of Internal Fraud Prevention Fund Management in Village - Mait, Margaretha S. N.; Mandagi, Marthinus; Dilapanga, Abdul Rahman (Technium Social Sciences Journal, 2021)
Since regional autonomy in 2004, it has brought major changes in government administration in Indonesia. The decentralization policy has changed—the system of governance shift from previously centralized to decentralized. Tomohon City is one of the autonomous regions where the government strives to provide maximum service to the community, especially developing development. The purpose of this article is to discuss the role of the government's internal supervisory apparatus in preventing fraud in the management of village funds. This study uses a qualitative approach—data collection techniques using interviews, observation, and documentation. The data analysis technique uses the stages of data reduction, data presentation, and verification. The results showed that the role of the Tomohon City Inspectorate was as Fraud Prevention in the Management of Village Funds, (1) Quality Assurance. The role of the Tomohon City Inspectorate in quality assurance (performed through an audit, monitoring, review, evaluation, and other supervisory activities. (2) Providing advice. The role of the government's internal supervisory apparatus is to provide an objective and independent assessment of the feasibility of the governance structure and the effectiveness of government organizations/agencies. (3) Providing early warning that is early detection of problems that occur in each agency before other parties find out. They are required to provide solutions and formulate anticipatory steps so that problems that occur do not occur.